THE PHARMACIST'S ASSESSMENT ON PATIENTS WHO CONSUME SUPPLEMENTS AND HERBAL WHILE UNDERGOING WARFARIN THERAPY - Djunaedi, Mochamad; Azhar Syed Sulaiman, Syed (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The supplements and herbal medicines used should be monitored in a patient taking warfarin, to achieve the goal of warfarin anticoagulation. This study aims to evaluate the impacts of the supplement and the herbs used on the performance of anticoagulation. Methods: There were 214 eligible patients for having CHADS2 score >2 registered at warfarin-medication therapy adherence clinic coordinated by Cardiac Hospitals in Malaysia in 2012 included for this study. They have been assessed using a trained pharmacist regarding the safety and efficacy of warfarin as per guideline. Results: Supplements and herbs are commonly used by the patient (61.2%) who is taking warfarin. Some patients (23%) have decided not to use or stop using it after being consulted by the pharmacist. Some are even starting to use it (37%). Effects of supplements and herbal medicines were found to decrease in the International normalized ratio (INR) reading as 33%, increasing in 37% the INR reading. Further, pharmacist action is to do a dose adjustment to reach INR in the therapeutic range 2.0–3.0. Supplements consumed as categorized as phytomedicine-containing herbs, such as Omega3 and glucosamine. Whereas herbs used as beetle leaves and the product of extracted herbs, for example, Gingko biloba, Cordyceps, etc. Conclusion: Monitoring by pharmacist is needed to achieve the goal of warfarin as well as to minimize the INR out of therapeutic. The use of herbal and supplement is found to be a factor contributes to the performance of anticoagulation control which has been successfully achieved 71.2%.